Betavoltaic study of a GaN p-i-n structure grown by metal-organic vapour phase epitaxy with a Ni-63 source - Kuruoglu, Neslihan Ayarci; Ozdemir, Orhan; Bozkurt, Kutsal (ELSEVIER SCIENCE SA, 2017)
Galliumnitride in a p-i-n structure grown by metal-organic vapour phase epitaxy was exposed to nickel-63 beta particle radiation to understand the betavoltaic properties. The effect of the radiation was monitored by performing current density-voltage measurements in conjunction with capacitance-voltage measurements. Interestingly, a betavoltaic effect with a short circuit current density of 1.2 nA/cm(2) and open circuit voltage of 300 mV, leading to a conversion efficiency of 0.0119% was observed. Though the thickness of the sample layers was carefully tuned for betavoltaic radiation, the extracted efficiency was evaluated as less than unity in percent. The reason for achieving poor conversion efficiency might be related to backscattering issues and to the presence of a gap between the source and the sample as these factors were not included in the efficiency calculation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Betavoltaic; GaN p-i-n diode; Trap-assisted tunnelling; Weighted average thickness; GALLIUM NITRIDE; DESIGN; SENSOR; SIMULATION; CELL; Materials Science; Physics